The Medical Library Association guide to developing consumer health collections - Joseph, Claire B. 1953- (Medical Library Association books, 2018)
"This authoritative book guides both library graduate school students and seasoned librarians from academic, health sciences, and public libraries, to develop, maintain, nurture, and advertise consumer health collections. It covers all that is involved in developing a new consumer health library"-- Provided by publisher.